(Re‐)Locating the Local and National in the Global: Multi‐Scalar Political Alignment in Transnational European Dockworker Union Campaigns. (6th April 2017) - Fox‐Hodess, Katy
Abstract: Labour activists have called for greater international co‐ordination among trade unions in response to the assault on organized labour by global capital, but such co‐ordination faces many hurdles. Under what conditions can unions overcome those barriers and co‐ordinate effectively to achieve campaign goals? I examine this question through a comparison of European‐level international solidarity with Portuguese, Greek and English affiliates of the International Dockworkers Council involved in labour disputes. The divergent outcomes of otherwise similar cases reveal the critical role of politics and strategy at different scales and sites of union organization in determining the successful exercise of labour internationalism.